Energy imbalance and its association with obesity among medical students: a cross-sectional evaluation of dietary intake and physical activity - Chudamani, Sandeep Kumar; Bahinipati, Jyotirmayee; Mohapatra, Rg Asutosh; Padhee, Sourav; Mahapatra, Srikrushna (International Journal of Research in Medical Sciences, 2026)
Background: Excess energy intake and insufficient energy expenditure are the fundamental factors in the development of obesity. Due to demands of rigorous academic schedule, irregular eating patterns, consumption of convenience foods and limited time for involvement in physical activities, medical students are at risk for development of obesity. Implications of these are quite significant as it increases the risk for metabolic syndrome and cardiovascular disorders. Considering these, this study was done to evaluate factors responsible for excess calorie intake which can further add to targeted interventions. Methods: 264 undergraduate students were included in the study. 24 hrs recall, monthly FFQs, data on fast food intake including energy spent for physical activity were collected by questionnaire approved by NIN, ICMR. Based on BMI they segregated into normal, overweight and obese. DEI, DEE and energy spent in physical activities were calculated by standardized formulae. Excess energy was calculated (DEI-DEE) Kcal/day. Correlation and regression statistical analysis were done to identify the risk factors for excess calorie intake. Results: Excess calorie intake was significantly higher in overweight and obese individuals. Linear regression analysis showed physical activity significantly affecting BMI (p<0.001) (95% CI= 2.87-4.06). Conclusions: Body weight is thus dependent upon amount of calorie intake and its balance with energy expenditure with physical activity playing a significant role in maintaining healthy weight.